Trypanotolerance and the value of conserving livestock genetic resources - Trail, J.C.M.; D'Ieteren, G.D.M.; Teale, A.J. (Canadian Science Publishing, 1989)
Summarises the impact of trypanosomiasis on development of trypanotolerant livestock. Describes current genetic research being carried out by collaborating national and international organisations in the African Trypanotolerant Livestock Network, and discusses the importance of conserving these genetic resources to Africa.